Analisis Pengaruh Rencana Pelaksanaan Pembelajaran Terhadap Kualitas Pembelajaran - Diva Dhiyaul Auliyah; Sevia Rahayu Nur Habibah; Rosaliana; Faelasup, Faelasup (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2024)
The influence of lesson plans is a crucial aspect in the educational context, playing an important role in improving the quality of learning. Lesson plans are structured guides used by teachers to plan and manage the learning process in the classroom. By adhering to curriculum and syllabus standards, lesson plans assist teachers in customising appropriate learning strategies to the needs and abilities of learners. This includes not only the development of subject matter but also innovative approaches to facilitate deep understanding and strengthening of learners' competencies. This study aims to analyse the effect of lesson plans on learning quality. The method used by the author in this research is a qualitative method with a literature review approach. Learning Implementation Plan (RPP) has a very important role in determining the quality of learning in schools. Well-constructed lesson plans based on the applicable curriculum can provide clear direction in the learning process, from planning, and implementation, to evaluation. Effective implementation of lesson plans can increase learner engagement and understanding, as well as assist teachers in developing learning strategies that suit the needs and characteristics of learners.